A Review of the Potential Health Benefits of Low Alcohol and Alcohol-Free Beer: Effects of Ingredients and Craft Brewing Processes on Potentially Bioactive Metabolites - Duane D. Mellor; Bishoy Hanna-Khalil; Raymond Carson (Beverages, 2020)
Beer is a beverage of significant historical and cultural importance. Interest in the potential health effects of alcoholic beverages has largely focused on wine; however, there are a number of potentially beneficial bioactives that beer may contain that warrant further investigation. The challenge of considering any potential health benefits of beer are restricted by the negative consequences of its alcohol and energy content. There is potential to enhance the bioactive qualities of beer whilst reducing the alcohol and energy content through novel brewing approaches often used in craft brewing, in terms of ingredients, brewing methods and type of fermentation. Consumer demand to produce a greater variety of beer types, including alcohol-free beers, may also help to increase the number of beers which may have greater potential to improve health, with lower levels of alcohol, while still being tasty products. As low alcohol, prebiotic and bioactive containing beers are developed, it is important that their potential health benefits and risks are fully assessed.